2003
DOI: 10.1007/s00240-003-0329-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of renal damage by alpha tocopherol in ischemia and reperfusion models of rats

Abstract: Ischemia-reperfusion injury in rat kidneys most probably comes from oxidative stress, but the possible preventive effect of alpha-tocopherol (AT) treatment on this injury has not yet been established. Forty male Wistar rats were randomly divided into four groups. The left renal arteries of all rats except the controls were clamped to induce renal ischemia. The left kidneys of the rats in the ischemia group were removed following 40 min ischemia. The rats in the ischemia-reperfusion and ischemia-reperfusion-AT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 31 publications
2
26
0
3
Order By: Relevance
“…Melatonin was administered 3 h and 15 min. prior to the renal ischemia in previous experimental ischemia-reperfusion models, [10,11,13] whereas in our study, melatonin was given 72 h, 48 h, 24 h, and 30 min before ischemia. Thus, our study is again different by the dosage of antioxidants, time of administration, and parameters studied.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Melatonin was administered 3 h and 15 min. prior to the renal ischemia in previous experimental ischemia-reperfusion models, [10,11,13] whereas in our study, melatonin was given 72 h, 48 h, 24 h, and 30 min before ischemia. Thus, our study is again different by the dosage of antioxidants, time of administration, and parameters studied.…”
Section: Discussionmentioning
confidence: 76%
“…However, the IR+Melatonin group findings were better than IR+vitamin E group. Avunduk et al [13] reported that in renal ischemia-reperfusion injury, vitamin E treatment prevented mitochondrial damage. Our IR+ vitamin E group findings were similar to this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results, thus, provided an important basis for the preventive effect of various antioxidants or free radical scavenging agents (Avunduk et al, 2003;Sehiril et al, 2003;Ohkita et al, 2005 and others) and ironchelators (e.g. desferrioxamine, Pincemail et al, 2000) on acute renal failure caused by ischemia or ischemia/ reperfusion.…”
Section: + -Catalyzed Fenton Reaction Is the Central Mechanism Of Thmentioning
confidence: 51%
“…13 Numerous studies suggest that ROS can cause direct cellular damage through protein oxidation and degradation, lipid peroxidation and DNA damage and lipid peroxidation is believed to be an important cause of the destruction and damage to cell structure and function. 4,[14][15][16][17] Oxidative stress-induced cell injury is not only mediated by increased ROS production, but also by a decreased antioxidant defense system. 14 SOD is a class of enzymes that prevents damage from ROS during normal conditions by converting superoxide into hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%